Toxic encephalopathy in a clinicl case of polycythemia vera - P. I. Kuznetsova; M. M. Tanashyan; A. A. Kornilova (Бюллетень сибирской медицины)
The article deals with a clinical case description of a female patient with toxic encephalopathy against the background of Ph-negative myeloproliferative diseases. The article discusses symptoms and neuroimaging of hepatic encephalopathy developed as a result of a shunt placed after portal vein thrombosis. The issues of etiology and pathogenesis of hepatic encephalopathy, principles of therapy, as well as the unique clinical picture of nervous system damage in this condition are also discussed. Data on the role of manganese in development of toxic encephalopathy, accumulation of paramagnetic substance in the basal ganglia of the brain and development of extrapyramidal symptoms are presented. The pathogenesis of toxic damage to neurons, increase in their sensitivity to hypoxia, and the relationship with the risk of cerebrovascular disorders and development of chronic cerebral ischemia, contributing to reduction of cognitive functions, are described.